2016
DOI: 10.25011/cim.v39i6.27501
|View full text |Cite
|
Sign up to set email alerts
|

Potential beneficial effects of foot bathing on cardiac rhythm

Abstract: Purpose: Foot bathing therapy is a simple technique that induces sensations of comfort and relaxation. The aim of this study was to examine the effect of foot bathing therapy on heart rate variability (HRV) parameters in a healthy population.Methods: Participants were twenty healthy female subjects (median age=20.67 years, SD=1.04). The recording ECG was applied for 5 minutes before and for 5 minutes after foot bathing therapy of 10 minutes. Subjects rested for 10 minutes without recording ECG in order to stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Hands and feet warm bathing is simple technique that induce (7) sensation of comfort and relaxation .Duygu et al showed that warm water footbaths led to relaxation by increase parasympathetic response and decrease sympathetic (8) response . Cal E et al reported hands and feet warm bathing can reduce signicant postoperative caesarean delivery (9) pain .…”
Section: Introductionmentioning
confidence: 99%
“…Hands and feet warm bathing is simple technique that induce (7) sensation of comfort and relaxation .Duygu et al showed that warm water footbaths led to relaxation by increase parasympathetic response and decrease sympathetic (8) response . Cal E et al reported hands and feet warm bathing can reduce signicant postoperative caesarean delivery (9) pain .…”
Section: Introductionmentioning
confidence: 99%